The impact of information presentation style on belief change: An experimental investigation of a Socratic Method analogue - Harrison, L.; Clark, G.; Rock, A.; Egan, Sarah (Wiley-Blackwell Publishing Ltd., 2018)
© 2018 The Australian Psychological Society Background: Cognitive behaviour therapy (CBT) employs a variety of psychological techniques and procedures with the aim of achieving cognitive change, such as in the strength of belief in dysfunctional cognitions. The present study aimed to investigate whether analogues of two commonly used CBT information presentation styles, Socratic Method, and didactic psychoeducation, differentially impacted upon the strength of a commonly held irrational belief. Method: Sixty-nine participants were recruited to participate in the online experimental study. Participants were allocated to one of the three conditions and presented with a 15-min intervention: an analogue of the Socratic Method, didactic psychoeducation, or non-relevant reading (the control condition). Measures of belief, anxiety, and behaviour relating to the target cognition were analysed pre- and post-intervention. Results: Results indicated significant change occurred in strength of belief from pre-to-post intervention across all three conditions. The Socratic analogue condition resulted in significantly greater belief change than the control condition, but did not display significantly greater belief change than the didactic psychoeducation condition. In contrast, the didactic psychoeducation condition did not display significantly different belief change than the control condition. Conclusions: The results of the study do not provide evidence of a clear superiority of an analogue of the Socratic Method relative to didactic psychoeducation, with regards to magnitude of belief change following a brief intervention. Despite a number of methodological limitations, the results of the present study do suggest that the impact of the Socratic Method on belief change warrants further investigation.